Respuesta :
Hello,
You should write y²-12y=-27 or y^2-12y=-27
y²-12y=-27
==>y²-2*6y+6²=-27+36
==>(y-6)²=9
(second answer)
You should write y²-12y=-27 or y^2-12y=-27
y²-12y=-27
==>y²-2*6y+6²=-27+36
==>(y-6)²=9
(second answer)
Answer: The correct option is
(B) [tex](y-6)^2=9.[/tex]
Step-by-step explanation: We are given to select the equation that is formed when completing the square on the following equation :
[tex]y^2-12y=-27~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
We will be using the following formula :
[tex]a^2-2ab+b^2=(a-b)^2.[/tex]
From equation (i), we have
[tex]y^2-12y=-27\\\\\Rightarrow y^2-2\times x\times6=-27\\\\\Rightarrow y^2-2\times x\times 6+6^2=-27+6^2\\\\\Rightarrow (y-6)^2=-27+36\\\\\Rightarrow (y-6)^2=9.[/tex]
Thus, the required equation that is formed is [tex](y-6)^2=9.[/tex]
Option (B) is CORRECT.